TANGGUNG JAWAB NOTARIS DAN PEGAWAI NOTARIS DALAM MENJAGA KERAHASIAAN AKTA - Lidia Sinaga; Madiasa Ablizar; Mahmul Siregar (LPPM Universitas HKBP Nommensen, 2021)
Notary is a Public Official who has the authority to make authentic deed, and is required to keep everything related to the deed they make confidential. In carrying out duties and positions, a Notary is generally assisted by a notary employee in preparing everything that is needed by a Notary in making a deed. The responsibility for the authentic deed remains the responsibility of the notary,if the notary employees leaks the deed made by the notary. Notary office employees who do not maintain the confidentiality of the deed by leaking the deed may be subject to witness Article 1365 of the Civil Code.Notaries can be held civilly responsible due to negligence in maintaining the confidentiality of deeds carried out by their employees, although in this case the notary does do direct faults.